Clinical characteristics of dermatomyositis patients with isolated anti-Ro-52 antibody associated rapid progressive interstitial lung disease: Data from the largest single Chinese center. (August 2019) - Chen, Fang; Zuo, Yu; Li, Shanshan; Shi, Jingli; Wang, Guochun; Shu, Xiaoming
Abstract: Aim: To describe and expand the phenotype of isolated anti-Ro-52-associated rapid progressive interstitial lung disease (RP-ILD) in Dermatomyositis(DM) in Chinese patients. Methods: 491 patients with PM/DM-ILD hospitalized in the China-Japan Friendship Hospital from 2000 to 2017 were screened retrospectively. All proven cases of isolated anti-Ro-52-associated RP-ILD were selected for inclusion. The clinical features in this group were recorded. Results: Isolated Ro-52 antibodies existed in 20 PM/DM-ILD patients. Among them 5 patients developed RP-ILD. The 5 patients had typical rashes including Gottron's sign (80%), Helitrope rash (80%) and mechanic's hands (100%), but only few patients (20%) had arthralgia and muscle weakness. All patients had elevated levels of serum ferritin and decreased counts of CD3 + T cells. The estimated high-resolution computed tomography (HRCT) patterns of the five patients showed organizing pneumonia (OP) while RP-ILD patients without Ro-52 antibodies and non-RP-ILD patients with isolated Ro-52 antibodies mainly showed non-specific interstitial pneumonia (NSIP) patterns(P < 0.05). Although one patient died of infection after one month, 80%(4/5) of patients had good response to glucocorticoid treatment and these four patients survived were all alive at the end of follow-up. The survival rate in this group was the highest than those in RP-ILD patients with other myositis specific autoantibodies though the difference had no statistically significance. Conclusions: A small group of patients with isolated anti-Ro-52 antibody in DM could develop RP-ILD, which mainly presented OP on HRCT. Patients with isolated anti-Ro-52 antibody associated RP-ILD responded well to therapy and had good prognosis in DM. Highlights: A small group of DM-ILD patients with isolated anti-Ro-52 antibody can develop RP-ILD. The pathological pattern in this group of patients is OP. They had a good response to therapy with a relatively favorable prognosis.